Hook1 inhibits malignancy and epithelial–mesenchymal transition in hepatocellular carcinoma - Xu Sun; Qi Zhang; Wei Chen; Qida Hu; Yu Lou; Qi-Han Fu; Jing-Ying Zhang; Yi-Wen Chen; Long-Yun Ye; Yi Wang; Shang-Zhi Xie; Li-Qiang Hu; et al. (Tumor Biology)
Hook1 is a member of the hook family of coiled-coil proteins, which is recently found to be associated with malignant tumors. However, its biological function in hepatocellular carcinoma is yet unknown. Here, we evaluated the Hook1 levels in human hepatocellular carcinoma samples and matched peritumoral tissues by real-time polymerase chain reaction. Small interfering RNA knockdown and a transforming growth factor-β-induced epithelial–mesenchymal transition model were employed to investigate the biological effects of Hook1 in hepatocellular carcinoma. Our results indicated that Hook1 levels were significantly lower in hepatocellular carcinoma tissues than in the peritumoral tissues. In addition, Hook1 expression was significantly associated with hepatocellular carcinoma malignancy. Hook1 was downregulated after transforming growth factor-β-induced epithelial–mesenchymal transition. Moreover, Hook1 knockdown promoted epithelial–mesenchymal transition and attenuated the sensitivity of hepatocellular carcinoma cells to doxorubicin. In summary, our results indicate that downregulation of Hook1 plays a pivotal role in hepatocellular carcinoma progression via epithelial–mesenchymal transition. Hook1 may be used as a novel marker and therapeutic molecular target in hepatocellular carcinoma.